Pengaruh Pengungkapan Laporan Tahunan Periode 2014-2018 dan Ukuran Perusahaan Terhadap Harga Saham. (Studi Kasus Pada Perusahaan BUMN yang Sahamnya Terdaftar Dalam IDX BUMN20) - Demetrius Kunto Wibisono; Esther Yolanda (Universitas Kristen Maranatha, 2020)
This study aims to find out how the influence of Disclosure of Financial Statements for the period 2014 - 2018 and Company Size on the Stock Price. This case study was conducted by taking a sample of companies list on IDX BUMN20. This study uses the hypothesis testing method using IBM SPSS Statistics Subscription version 23. Based on the results of the study found that an increase in average disclosure in all companies listed on the IDX, in other words, an increase in awareness of the management of companies listed on the IDX to report both financial and non-financial information to the public. In addition, companies listed on the IDX are increasingly obedient to the policies made by the regulator (OJK) related to the disclosure of financial statements. The Annual Disclosure Variable does not partially affect the company's stock price, this is due to differences in the research sector and research year. Partially, the variable size of the company has an influence on stock prices, this is because investors are interested in investing in companies that have large assets and have a large market capitalization because they are considered more profitable. Simultaneously, the Annual Report Disclosure variable and company size variables have a significant effect on stock prices. Keywords: Annual Report Disclosure, Company Size, and Stock Price.